2014
DOI: 10.9775/kvfd.2014.10947
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Estrous Cycle on Oxidant and Antioxidant Parameters in Dairy Cows

Abstract: Reactive oxygen species have fundamental roles in reproductive functions. To comprehensively evaluate the relation between reactive oxygen species and infertility, physiological variations across the estrous cycle in healthy cows have to be known. For this purpose 25 healthy multiparous Holstein dairy cows having regular estrous cycles were used. The estrous cycles were synchronized by ovsynch protocol. Oxidant [lipid hydroperoxide (LOOH), total oxidant status (TOS), oxidative stress index (OSI)], antioxidant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…For example, Aksu et al [22] conducted a study on cows in which the use of CIDR in the synchronization protocol resulted in higher MDA levels than in those cows for which the devices were not used. Other studies conducted on cattle found that TAC and TOC levels were higher during the period of the cycle which had high progesterone levels than they were during the estrus period [3,23] . It has also been reported that estrogen and progesterone can affect OS parameters in the body [2] .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…For example, Aksu et al [22] conducted a study on cows in which the use of CIDR in the synchronization protocol resulted in higher MDA levels than in those cows for which the devices were not used. Other studies conducted on cattle found that TAC and TOC levels were higher during the period of the cycle which had high progesterone levels than they were during the estrus period [3,23] . It has also been reported that estrogen and progesterone can affect OS parameters in the body [2] .…”
Section: Introductionmentioning
confidence: 83%
“…Aydilek et al [3] conducted a study in which they attempted to measure TAC and TOC levels at various points of the reproductive cycle in cows. The study identified an increase in both factors during the estrus period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest RT was in phase IV, while the lowest was in phase II, and there was a significant interaction between estrus phases and hot conditions to exert this significant amendment. The estrous cycle is related to many physiological, metabolic, and hormonal variations (Aydilek et al, 2014), leading to diverse changes according to the estrus stage. The rise in RT during phase IV compared with phase II is explained by the corpus luteum that is fully functional during this stage and the increase in blood concentration of some hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative and antioxidative parameters were measured in the tissue samples using the Aeroset automated analyzer (Abbott, IL, USA) and a spectrophotometer (Cecil 3000, Cambridge, UK). The lipid hydroperoxide level (LOOH) was evaluated by the fluorometric method based on the reaction between malondialdehyde (MDA) and thiobarbituric acid [18]. All analyses were made in the Biochemistry Laboratory of the Faculty of Medicine at Harran University.…”
Section: Analyses Of Oxidant and Antioxidant Parametersmentioning
confidence: 99%